How to use the library [videorecording] an introduction ([New York] H.W. Wilson, 1989)
This program teaches users how to begin basic research using the three basic types of library resources commonly found in a library, namely 1. card catalog (or its electronic equivalent), 2. periodical indexes, 3. general reference and information sources (almanacs, dictionaries, vertical file, etc.).
VHS
Keywords: Catalogs, Card; Periodicals -- Indexes; Library science